2022
DOI: 10.3389/fgene.2022.805880
|View full text |Cite
|
Sign up to set email alerts
|

A Pan-Cancer In Silico Analysis of the COVID-19 Internalization Protease: Transmembrane Proteaseserine-2

Abstract: The new coronavirus (2019-nCoV) is an emerging pathogen that can cause severe respiratory infections in humans. It is worth noting that many of the affected COVID-19 patients have malignant tumors. In addition, cancer has been identified as a personal risk factor for COVID-19. Transmembrane proteaseserine-2 (TMPRSS2) is a crucial host protease that mediates S protein activation and initially promotes virus entry into host cells. Moreover, it is abnormally expressed in a variety of tumors. However, the systemat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 33 publications
0
2
0
Order By: Relevance
“…Then we obtained the first 100 targeted genes related to CDKN3 based on data sets by using the "Similar Gene Detection" module of GEPIA2. In addition, the "Gene_Corr" module of TIMER 2.0 provided heat map data of selected genes [ 39 ]. The Kyoto Encyclopedia of Genes and Genomes (KEGG) and Gene Ontology (GO) path analysis were performed and accomplished [ [40] , [41] , [42] ].…”
Section: Methodsmentioning
confidence: 99%
“…Then we obtained the first 100 targeted genes related to CDKN3 based on data sets by using the "Similar Gene Detection" module of GEPIA2. In addition, the "Gene_Corr" module of TIMER 2.0 provided heat map data of selected genes [ 39 ]. The Kyoto Encyclopedia of Genes and Genomes (KEGG) and Gene Ontology (GO) path analysis were performed and accomplished [ [40] , [41] , [42] ].…”
Section: Methodsmentioning
confidence: 99%
“…Given the inflammatory nature of cancer, other infectious diseases and the cytokine storm seen in COVID-19 positive patients, studies reported elevated levels of cytokines and TNF-α in severe COVID-19 cases [12][13][14][15], suggesting cancer patients can be more prone to develop COVID-19 disease. Also, various viral entry, processing and endosomal route protein were detected to be elevated in pancancer samples in comparison to their healthy control [16][17][18]. Furthermore, pan-cancer studies revealed that SARS-CoV-2 associated genes, namely ACE2, TMPRSS2, TMPRSS4, were found to be upregulated in a number of TGCA samples [4,5,19,20], indicating an interplay between cancer and SARS-CoV-2 infection.…”
Section: Introductionmentioning
confidence: 95%